Effects of Mechanical Stretch on Cell Proliferation and Matrix Formation of Mesenchymal Stem Cell and Anterior Cruciate Ligament Fibroblast. (25th July 2016) - Sun, Liguo; Qu, Ling; Zhu, Rui; Li, Hongguo; Xue, Yingsen; Liu, Xincheng; Fan, Jiabing; Fan, Hongbin
Abstract : Mesenchymal stem cells (MSCs) and fibroblasts are two major seed cells for ligament tissue engineering. To understand the effects of mechanical stimulation on these cells and to develop effective approaches for cell therapy, it is necessary to investigate the biological effects of various mechanical loading conditions on cells. In this study, fibroblasts and MSCs were tested and compared under a novel Uniflex/Bioflex culture system that might mimic mechanical strain in ligament tissue. The cells were uniaxially or radially stretched with different strains (5%, 10%, and 15%) at 0.1, 0.5, and 1.0 Hz. The cell proliferation and collagen production were compared to find the optimal parameters. The results indicated that uniaxial stretch (15% at 0.5 Hz; 10% at 1.0 Hz) showed positive effects on fibroblast. The uniaxial strains (5%, 10%, and 15%) at 0.5 Hz and 10% strain at 1.0 Hz were favorable for MSCs. Radial strain did not have significant effect on fibroblast. On the contrary, the radial strains (5%, 10%, and 15%) at 0.1 Hz had positive effects on MSCs. This study suggested that fibroblasts and MSCs had their own appropriate mechanical stimulatory parameters. These specific parameters potentially provide fundamental knowledge for future cell-based ligament regeneration.